2015
DOI: 10.18359/rfcb.384
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Signaling Between Guava (Psidium guajava L., Myrtaceae) and the Guava Weevil (Conotrachelus psidii Marshall)

Abstract: <div class="WordSection1"><p class="Default"> Volatile organic compounds (VOCs) from guava (<em>Psidium guajava </em>L.) reproductive tissues (flower bud, open flower, petal fall, fruit setting, and fruit growth) were collected <em>in situ </em>during the day by headspace-solid phase microextraction (HS-SPME), and from flower bud and fruit setting by dynamic headspace (DHS). The samples were analyzed by GC-MS to separate and identify VOCs produced by guava, which potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…These compounds were present in all of the guava reproductive tissues, being quantitatively relevant in flower buds and fruit setting, the two guava stages where C. psidii is found. 11) Other terpenes, such as α-copaene, α-humulene and aromadendrene, were detected only by DHS and mainly on male insects (except for α-humulene).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…These compounds were present in all of the guava reproductive tissues, being quantitatively relevant in flower buds and fruit setting, the two guava stages where C. psidii is found. 11) Other terpenes, such as α-copaene, α-humulene and aromadendrene, were detected only by DHS and mainly on male insects (except for α-humulene).…”
Section: Resultsmentioning
confidence: 96%
“…Once transferred to the laboratory, individuals were segregated by sex according to the procedure reported by Silva-Filho et al, 13) and maintained separately in plastic boxes at 20 ± 2°C, at a relative humidity of 80 ± 10% with pieces of green guava fruits as food and 12-h light regime. 11) Insect volatile collection.…”
Section: Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in our case, copaene, caryophyllene, and aromadendrene were observed in tissues of fruit setting of Colombian pink guava, whereas terpineol and the farnesene isomers were not observed by the authors. [14] In our study, the emission of caryophyllene by fruit setting was low (2 %) in comparison to that of other volatiles such as hexanal, nonanal, limonene, and cis-3-hexenyl acetate. [18] But in the case of Colombian guava, the emission of limonene was low (5 %) with respect to other compounds.…”
Section: Volatile Compounds Emitted By Immature Guava Fruits In Fieldmentioning
confidence: 56%
“…Authors reported β-caryophyllene, limonene, and copaene as the main volatile organic compounds involved in the signalization between Conotrachelus psidii Marshall and its host, the Colombian guava. [14] The mentioned compounds are produced during the phenological stages of flower bud and fruit setting. On the other side, papayanol and papayanal were identified as volatile compounds released by C. psidii that play the role of aggregation pheromone.…”
Section: Introductionmentioning
confidence: 99%